2010
DOI: 10.1161/circep.109.931634
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillatory Conduction in the Atrial Free Walls of Goats in Persistent and Permanent Atrial Fibrillation

Abstract: Background-Over a time course of months, the stability of atrial fibrillation (AF) gradually increases and the efficacy of pharmacological cardioversion declines both in humans and in animal models. Changes in fibrillatory conduction over this period largely are unexplored. Methods and Result-Goats were instrumented with an atrial endocardial pacemaker lead and a burst pacemaker. AF was maintained for 3 weeks (short-term AF [ST], nϭ10) or 6 months (long-term AF [LT], nϭ7). AF could be cardioverted pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 31 publications
4
82
0
1
Order By: Relevance
“…The limited data available from chronic AF studies of Ͼ3 mo of AF have demonstrated that whereas electrical remodeling occurs in hours to days, structural remodeling occurs over weeks to months. Recent studies (14,15,26,27) have shown that important conduction changes and structural remodeling occur as AF persists from a few weeks to several months in duration. Eckstein et al (14) studied the time course of structural and electrophysiologic remodeling in goats at baseline and after 3 wk and 6 mo of RAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited data available from chronic AF studies of Ͼ3 mo of AF have demonstrated that whereas electrical remodeling occurs in hours to days, structural remodeling occurs over weeks to months. Recent studies (14,15,26,27) have shown that important conduction changes and structural remodeling occur as AF persists from a few weeks to several months in duration. Eckstein et al (14) studied the time course of structural and electrophysiologic remodeling in goats at baseline and after 3 wk and 6 mo of RAP.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that "AF begets AF," or, in other words, the longer AF persists, the more likely it is that a patient will experience more AF in the future (30). Numerous studies (1,8,24,29,33,34) have demonstrated that there are significant structural and electrophysiological substrate changes that accompany chronic AF.Recent studies (14,15,26,27) have shown that whereas electrical remodeling and sustained AF may be achieved in a matter of weeks, tissue levels and structural remodeling continue over months. Patients with longstanding persistent AF exhibit different activation patterns and have higher AF recurrence rates than patients with paroxysmal AF (11,25,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although AF could be terminated pharmacologically after few weeks, it could not be drug cardioverted after 6 months. 23 Based on these works, the prevailing mechanism of AF remodeling in humans is thought to be the multiplication of randomly circulating waves associated with a decreased atrial refractory period and heterogeneous tissue structure. The current study suggests different time-critical mechanisms for persistent AF in humans.…”
Section: Progressive Remodeling Of Atrial Tissue With Af Continuationmentioning
confidence: 99%
“…2,3 Advocates of this high spatial resolution mapping argue that the answer lies in the microscopic detail. That high resolution mapping has revealed evidence of endocardial-epicardial dissociation, 4 complex fibrillatory waves, 5 and longitudinal dissociation of myofibrils (Figure 1) 3,6 suggests that the causative mechanism is anarchical and perpetuated by generalized, diffuse processes, leading to widely distributed, complex microreentry. This is portrayed as a completely different concept from that revealed by mapping that is necessarily global and simultaneous, albeit of low spatial resolution.…”
Section: Rotors: From Macroscopic To Microscopicmentioning
confidence: 99%